Regulation of intramitochondrial cholesterol transfer to side-chain cleavage cytochrome P-450 in rat adrenal gland. - Privalle, C T (1983)
Rat adrenal mitochondria accumulated cholesterol during ether stress in vivo when side-chain cleavage was inhibited by aminoglutethimide (control = 14.6 vs. aminoglutethimide = 26.5 micrograms of cholesterol per mg of protein). This accumulation was insensitive to simultaneous administration of cycloheximide (24.2 micrograms/mg), but side chain cleavage in the mitochondria was greatly decreased. Outer and inner mitochondrial membrane fractions were separated by discontinuous Ficoll gradient centrifugation. Quantitation of marker enzymes for inner, outer, and microsomal enzymes indicated that outer membranes contained less than 5% inner membranes. The inner membrane fraction contained less than 7% outer membrane and included 90% of mitochondrial cytochrome P-450. Electron microscopy revealed outer membranes as circular intact ghosts, whereas inner membranes were largely intact and retained vesicular structure typical of intact adrenal cortex mitochondria. Administration of aminoglutethimide effected a 2-fold increase in inner membrane cholesterol (9.4 vs. 20.1 micrograms/mg) but simultaneous administration of cycloheximide completely blocked this increase (10.9 micrograms/mg). We conclude that: (i) in the presence of aminoglutethimide, stress stimulates accumulation of cholesterol in the inner membrane of adrenal mitochondria; and (ii) transfer of cholesterol from outer to inner membranes requires a cycloheximide-sensitive agent.